O novo Exame Nacional do Ensino Médio – Enem e suas relações com a educação CTS e com o ensino de biologia - Franco, Alexandre Neves (2022)
The present research has had as its focal point the features of the Exame Nacional do Ensino Médio (Enem), linked to Biology and to the Science, Technology and Society Education (STS Education). Its genesis arose from the following question: the components of the new Enem (2009 to 2018), related to Biology, retain similarities with the educational assumptions STS, as well as were assembled observing the Competences (C) and Abilities (A) that are part of the Enem Matrix Reference, in the area of Nature and Technology Sciences (RM-Enem/CNT? And, how are the Instituto Federal do Tocantins (IFTO) Biology teachers, who lecture in the Ensino Médio (EM) are putting together their contents so they would correspond to the official documents requirements? With the purpose of acknowledging the problem of the investigation, the succeeding general objective was presented: to examine how the STS Education, likewise the C and A of the RM-Enem/CNT are concatenated with the issues associated to the Biology that are applied in the new Enem, and in which manner the IFTO Biology teachers, who teach in the EM, carry out their works to meet that demand on the students’ development. Years of experience in quite a few teaching modalities enable myself to infer a priori the thesis that the aspects of the new Enem linked to Biology maintain some alikeness with the STS educational proposals, and with the C and A of the RM-Enem. Also, the IFTO Biology teachers who work in the EM, seek to fit together the program contents to the official documents, to the RM –Enem and to the STS Education. The methodological approach is of a qualitative kind, that also presents quantitative data. In order to achieve the data, there has been adopted the indirect documentation (documental and bibliographical research) and direct documentation. That direct documentation is of an extensive direct observation style, using the structured questionnaire modality (SQ), which was applied to eleven IFTO Biology teachers, who strive in the technical course combined with the EM. The data obtained from the documental and bibliographical researches show a disconsonant distribution of the Biology contents, with prepoderance of themes related to ecology/environment, be it analyzing in a compartmentalized manner (sub-areas), be it in a more interdisciplinary way, based on the Objects of Knowledge (OK) of the RMEnem/CNT. Most of the C and A were identified on the items associated to Biology, pointing out an important connection. In respect to the closeness of the aspects linked to the Biology with the STS Education, the study disclosed that the majority of the items (66,8%) presented some type of proximity. Nonetheless, if we consider a more intense adjacency, the items become a minority (18,5%). In general, the participants of the research exposed to have some knowledge of the official documents, of the RMEnem/CNT and of the STS educational proposals, even looking for ways of including their precepts in their pedagogical práxis. Yet, they admit that the students’ greater interest, even though they are in a technical course integrated to the EM, is the University entrance examination, mainly the Enem. Their main concern is not a citizen formation focusing on the preparedness for life and work, as the official documents uphold.